Continuous Renal Replacement Therapy With Adsorbing Filter oXiris in Acute Kidney Injury With Septic Shock: A Retrospective Observational Study - Guan, Mingjing; Wang, Hao; Tang, Xin; Zhao, Yuliang; Wang, Fang; Zhang, Ling; Fu, Ping (Frontiers in Medicine, 2022)
Background and objective: Sepsis/septic shock-associated acute kidney injury (S-AKI) is associated with prolonged kidney recovery and extremely high mortality. Extracorporeal blood purification therapy for the removal of endotoxin and cytokines might benefit patients with S-AKI. The purpose of this study was to compare the efficacy of adsorbing filter oXiris in the treatment of S-AKI. Design, setting, participants, & measurements: This was a retrospective observational study conducted from September 2017 to June 2020 in ICU. All patients received CRRT for ≥24 h. The primary outcomes were mortality. The secondary outcomes included cardiovascular SOFA score and vasoactive-inotropic score (VIS), the SOFA ,the reduction of inflammatory mediators. Results: A total of 136 septic shock patients with AKI were included. The interventional group (oXiris group; n=70) received CRRT with endotoxic and cytokine adsorption function hemofilter (oXiris), while the control group (ST150 group; n=66) was treated with the ST150 hemofilter. The early mortality in 7 and 14 days was significantly lower in oXiris group compared with ST150 group (7 days: 47.3% vs. 74.3%, P=0.007; 14 days: 58.8% vs. 80.3%, P=0.005), but the difference was not significant in 90-day mortality (71.4% vs. 81.8%, P=0.160). Additionally, the reduction of the SOFA score in the oXiris group at 24 h, 48 h, and 72 h CRRT was significantly faster than that in the controlled group. Meanwhile, the reduction of VIS score in the oXiris group compared with the ST150 group at 24 h and 48 h after the initiation of CRRT was statistically significant (P<0.05). Furthermore, the decreases in procalcitonin were greater in the oXiris group than those in the ST150 group at 24 h, 48 h, and 72h after initiation of CRRT.Multivariate Cox regression model demonstrated that oXiris (vs.ST150) played a favourably important role in the prognosis of septic shock patients with a hazard ratio (HR) of 0.500 (95% CI: 0.280-0.892; P=019). Conclusions: Although no difference was found in 90-day mortality, oXiris might reduce the short-term (<14-day) mortality compared with ST150 groups in septic shock with AKI. Further investigation in randomized controlled trials or high-quality prospective studies is warranted to validate the present findings.